Iron therapy for the treatment of preoperative anaemia in patients with colorectal carcinoma: a systematic review. (December 2015) - Borstlap, W. A. A.; Stellingwerf, M. E.; Moolla, Z.; Musters, G. D.; Buskens, C. J.; Tanis, P. J.; Bemelman, W. A.
Abstract: Aim: Preoperative anaemia is associated with increased morbidity and mortality. The aim of this systematic review is to evaluate the efficacy of preoperative iron supplementation in the treatment of anaemia, and its effect on the postoperative recovery of patients undergoing surgery for colorectal carcinoma. Method: This systematic review was performed using MEDLINE, EMBASE and the Cochrane library to assess current evidence on the role of iron supplementation in the treatment of preoperative anaemia. Our main outcomes were absolute increase in haemoglobin, blood transfusion rate and postoperative morbidity. Main inclusion criteria were: preoperative iron supplementation, presence of colorectal carcinoma and elective surgery. The Downs–Black questionnaire was used for quality assessment of the included studies. Results: Of the 605 studies analysed, seven, three randomized controlled trials and four cohort studies, were included. Despite iron supplementation, the three randomized controlled trials showed a decrease in haemoglobin level. This was contrary to the four cohort studies which all showed a significant increase. All studies showed a decreased blood transfusion rate following iron supplementation. None of the included studies assessed postoperative morbidity. Due to heterogeneity in study design, duration of treatment, dosages and variation in iron substrates, we were unable to perform a meta‐analysis. Conclusion: In anaemic patients who require surgery for colorectal carcinoma, current evidence is of inadequate quality to draw a definitive conclusion on the efficacy of the various measures to treat preoperative anaemia.